Legal Literacy Related to Processed Food Labels for Students at Madrasah Ibtidaiyah Darul Ulum Rejomulyo Magetan - Masnun, Muh. Ali; Sulistyowati, Eny; Nugroho, Arinto; Hermono, Budi; Azizah, Siti Nur; Faisol, Syahid Akhmad (Universitas Negeri Semarang, 2023)
labels aim to provide legal literacy for the target audience, namely MI Darul Ulum Rejomulyo students, Magetan Regency by looking at knowledge, understanding, attitudes and behavior of students before and after the activities given in the form of questionnaires and sheets observation. The results of the Community Service activities after the Community Service team provided legal literacy, showed that there was a significant increase in legal knowledge, legal understanding, and legal attitudes of students regarding the laws and regulations on processed food labels. However, the legal behavior still shows students who do not really care about processed food labels.